RANCANG BANGUN AUGMENTED REALITY PADA APLIKASI PEMBELAJARAN KOSAKATA BAHASA INGGRIS UNTUK SISWA SEKOLAH DASAR - Galih Aditya Dwisevi; Dadang Sujana; Muhammad Khoirul Anam (Universitas Islam Syekh Yusuf Tangerang, 2026)
English proficiency is an essential skill in the era of globalization, including for elementary school students who are building their basic vocabulary. Previous Augmented Reality (AR)-based studies mainly focused on material visualization and were limited to the development stage, without direct user testing. This study develops an AR-based English vocabulary learning application featuring three-dimensional objects, audio pronunciation, and interactive quizzes to enhance students’ motivation and comprehension. The application was developed using the ADDIE model with Unity and Vuforia, and implemented on Android devices. Feasibility testing was conducted through User Acceptance Testing (UAT) by teachers and End User Computing Satisfaction (EUCS) by 52 fifth-grade elementary school students. The UAT results indicated that all features functioned as designed, while the EUCS produced an average score of 4.36 (“Very Satisfied” category). This score is higher compared to students’ satisfaction with conventional learning, which tends to be monotonous, indicating that the application provides a more interactive, user-friendly, and effective learning experience.